OROPHARYNGEAL MANIFESTATIONS IN HIV INFECTED PATIENTS - Gabriela Juganariu; Manciuc Carmen; Cristina Nicolau; Andrei Vata; Liviu Prisacariu; Carmen Dorobat (Romanian Society of Oral Rehabilitation, 2011)
Objectives: We aimed to determine the prevalence of oropharyngeal manifestations in HIV infected patients. Materials and methods: A retrospective study on 824 patients found in the evidences of the Infectious Diseases Clinic in Iasi, diagnosed in different stages of HIV infection and admitted to hospital between January the 1 st and December the 31st of 2010. Results: Oropharyngeal manifestations appeared in less than half of all patients (43.4%), the majority of which were between 15 and 24 years old (66.3%). The most frequent lesion was oral candidiasis 72.19%, followed by gingivostomatitis 72 cases (20.24%), infections with herpes virus 13 cases (3.65%), aphthous stomatitis 11 cases (3,08%), Kaposi's sarcoma 2 cases and hairy leukoplakia 1 case. Oral lesions were associated mostly with the degree of imunosupresion and the level of CD4 cells. Conclusions: The degree of imunosupresion correlates significantly with the manifestations of oral infections, especially in patients suffering from candidiasis and with Kaposi's sarcoma. The oral lesions with the highest frequency spotted by our study were oral erythematous candidiasis and gingivostomatitis.